Theta-burst Transcranial Magnetic Stimulation Alters the Functional Topography of the Cortical Motor Network - Noh, NA; Fuggetta, G; Manganotti, P (Univ Sains Malaysia, SCH Medical Sciences, 2024)
Indexed by WOS/SCOPUS